2022
DOI: 10.3390/antibiotics11020258
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mechanisms of Vancomycin Resistance in Clostridioides difficile: A Systematic Review

Abstract: Antimicrobial resistance to treatments for Clostridioides difficile infection (CDI) poses a significant threat to global health. C. difficile is widely thought to be susceptible to oral vancomycin, which is increasingly the mainstay of CDI treatment. However, clinical labs do not conduct C. difficile susceptibility testing, presenting a challenge to detecting the emergence and impact of resistance. In this systematic review, we describe gene determinants and associated clinical and laboratory mechanisms of van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
(101 reference statements)
1
10
0
Order By: Relevance
“…The reason for the lack of vancomycin resistance in wild-type C. Instead, we have found that high expression of the vanG operon confers resistance to a low level of vancomycin (4 μg ml −1 ). Similar results have recently been obtained for C. difficile mutants isolated by serial passages in vitro in the presence of increasing concentrations of vancomycin and for several clinical isolates; however, all these strains contained additional mutations elsewhere in the chromosome (Eubank et al, 2022;Shen et al, 2020;Wickramage et al, 2021).…”
Section: Vancomycin Resistance and Vang Expressionsupporting
confidence: 85%
See 1 more Smart Citation
“…The reason for the lack of vancomycin resistance in wild-type C. Instead, we have found that high expression of the vanG operon confers resistance to a low level of vancomycin (4 μg ml −1 ). Similar results have recently been obtained for C. difficile mutants isolated by serial passages in vitro in the presence of increasing concentrations of vancomycin and for several clinical isolates; however, all these strains contained additional mutations elsewhere in the chromosome (Eubank et al, 2022;Shen et al, 2020;Wickramage et al, 2021).…”
Section: Vancomycin Resistance and Vang Expressionsupporting
confidence: 85%
“…Additional mutations may be needed to achieve higher level of resistance to vancomycin. Indeed, such mutations in other C. difficile strains with the increased resistance to vancomycin have been described (Eubank et al, 2022; Leeds et al, 2014; Shen et al, 2020; Wickramage et al, 2021; Zhou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As these Stickland reductases are cofactor-dependent, species-specific, and essential metabolic enzymes during disease, they have potential to be better pharmacological interventions in the age of antibiotic resistance. While vancomycin, fidaxomicin and metronidazole are standard antibiotic treatments for C. difficile , there is a high rate of infection reoccurrences and a high number of emerging hypervirulent strains resistant to standard care ( He et al, 2013 ; Eubank et al, 2022 ; Olaitan et al, 2022 ). In addition, these antibiotics don’t address the cause of infection—the imbalance of the microbiome—but rather combat the effects.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there are reliable data on oral vancomycin, as it is widely used in Clostridioides difficile infections. Few antibiotic resistances to vancomycin occurred over time, with a treatment duration of 10 days or even longer ( 52 54 ). However, recent experimental data demonstrated a significant role of Enterococci species in the pathogenesis of AL ( 25 , 55 ).…”
Section: Discussionmentioning
confidence: 99%